2018
DOI: 10.1007/s00417-017-3892-6
|View full text |Cite
|
Sign up to set email alerts
|

The levels of 12 cytokines and growth factors in tears: hyperthyreosis vs euthyreosis

Abstract: There are clear differences in the levels of cytokines and growth factors in the tears of healthy subjects and patients with GH without TAO. Tear cytokine changes and related dysfunctional tear syndrome (DTS) could be an early sign of occult TAO in Graves' hyperthyreosis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
2
10
0
1
Order By: Relevance
“…34 The level of IL-1α in the tear samples of GD patients, even without TED, was higher compared to controls. 35 Our previous finding, that PAI-1 concentration in the tear of TED patients is higher than in patients without TED 36 further supports the potential role of an IL-1α -PAI-1 interaction.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…34 The level of IL-1α in the tear samples of GD patients, even without TED, was higher compared to controls. 35 Our previous finding, that PAI-1 concentration in the tear of TED patients is higher than in patients without TED 36 further supports the potential role of an IL-1α -PAI-1 interaction.…”
Section: Discussionsupporting
confidence: 53%
“… 34 The level of IL-1α in the tear samples of GD patients, even without TED, was higher compared to controls. 35 Our previous finding, that PAI-1 concentration in the tear of TED patients is higher than in patients without TED 36 further supports the potential role of an IL-1α – PAI-1 interaction. The locally elevated cytokine level in the orbital connective tissue during TED development may lead to increased PAI-1 synthesis by orbital fibroblasts, and this process may be more marked in the presence of the 4G allele.…”
Section: Discussionsupporting
confidence: 52%
“…Furthermore, levels of IL-8, IP-10, and GM-CSF were significantly higher among patients with TSH concentrations < 0.4 mIU/L. Many different cytokines have been linked to autoimmune thyroid disease, such as IL-8 and IP-10, which in prior studies have been reported in Graves' disease and Graves' orbitopathy (13,14,(21)(22)(23). In fact, studies have suggested that IP-10 could be a good biomarker for disease severity in autoimmune thyroid disease (24).…”
Section: Discussionmentioning
confidence: 87%
“…A few points are worth noting when interpreting our findings. First, the investigated polymorphisms have found to be able to influence gene expression of corresponding cytokines, and altered mRNA expression levels of these cytokines have also been detected in patients with hyperthyroidism [54-56]. Thus, we speculated that these polymorphisms may affect gene expression levels of TNF-α/IL-1/IL-4/IL-6/IL-10 and then alter predisposition to hyperthyroidism.…”
Section: Discussionmentioning
confidence: 99%